Live football and tourism expenditure: match attendance effects in the UK. Issue 3 (26th May 2020) - Rudkin, Simon; Sharma, Abhijit
ABSTRACT: Research question: The inbound tourist expenditure generating role of football (soccer), particularly the English Premier League (EPL), is evaluated. An enhanced economic and management understanding of the role of regular sporting fixtures emerges, as well as quantification of their impact. Expenditure on football tickets is isolated to identify local economic spillovers outside the stadium walls. Research methods: Using the UK International Passenger Survey, unconditional quantile regressions (UQR) are used to evaluate the distributional impact of football attendance on tourist expenditures. Both total expenditure and a new measure which adjusts expenditures for football ticket prices are considered. UQR is a novel technique which is as yet underexploited within sport economics and management and confers important methodological advantages over both ordinary least squares and quantile regressions. Results and findings: Significant cross quantile variation is found. High spending football fans spend more, even after ticket prices are excluded. Surprisingly, spending effects owing to attendance are strongest for those who overall spend the least, confirming the role of sport as a generator of tourist expenditure. Though the attendance effect is smaller for higher aggregate spenders, there is nevertheless a significant impact across the distribution. Implications: Distributional expenditure impacts highlight clear differentials between attendance by high and low spenders. Similar analysis is applicable to other global brands such as the National Football League (NFL), in the United States (American football) and the Indian Premier (cricket) League. The EPL's global popularity can be leveraged for achieving enhanced tourist expenditure.